ARABIC LANGUAGE AND THE TRAINING OF NIGERIAN MUSLIM WOMEN - Ayuba, Mahmud Adesina (European Scientific Journal, ESJ, 2013)
One of the problems confronting Muslim women in Nigeria today is lack of good knowledge of Arabic and Islamic Studies. This is greatly affecting their roles to rear children that will contribute positively to the society. The glorious Qur’ān shows that women are competent by making them partners with men in the work of preaching (Da‘wah). A detailed knowledge of Islam is, therefore, needed and this made knowledge of Arabic language necessary for every Muslim woman. This work looked into the benefits of Arabic language and literature especially for women. Methodologies adopted in this study are historical, moral and sociological approaches. Our findings revealed that Arabic has become the religious language of all Muslims; male and female. It was also discovered that training of Muslim women in Arabic language greatly helps in the understanding of Islamic literature materials, particularly the Qur’ān, which was revealed in Arabic language. We also observed that the understanding of rules of law from the Qur’ān and Sunnah could only be derived if stylistic peculiarities of Arabic language are understood. In conclusion, the work recommended intensive training of Muslim woman in Arabic language and literature so as to justify her position as first school for children.